PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN PROFITABILITAS TERHADAP KUALITAS LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Prasita, Puspa (Jurusan Akuntansi FEB UNTAN, 2025)
This research aims to determine the effect of capital structure, liquidity, and profitability on earnings quality with company size as a moderating variable in pharmaceutical companies listed on the Indonesia Stock Exchange. The sample in this research was obtained using a purposive sampling method, and then eight companies were obtained in five years to get 40 company data for 2018 - 2022. The data analysis tool is descriptive statistics using multiple linear regression analysis methods and moderated regression analysis with the help of applications. SPSS 25. The research results show that (1) Capital structure has a significant effect on earnings quality, (2) Liquidity has a significant effect on earnings quality, (3) Profitability has a significant effect on earnings quality, (4) Company size cannot moderate the influence of capital structure on earnings quality, (5) Company size cannot moderate the influence of liquidity on earnings quality, (6) Company size can moderate the influence of capital structure on earnings quality.